The impact of reinsurance on the profitability of insurance companies An applied study on private insurance companies operating in Syria: The impact of reinsurance on the profitability of insurance companies An applied study on private insurance companies operating in Syria (Journal of Hama University, 2024)
This research aimed to test the impact of reinsurance on the profitability of the 12 private insurance companies operating in Syria during the period 2009-2021. This is based on annual data obtained from the financial statements of the studied companies and reports of the Insurance Supervisory Authority. The dependent variable was measured by return on assets (ROA), while the independent variables were measured by: reinsurance ratio (PCR), insurance dependence ratio (RDC). Reinsurance price (REP), company size (SIZE), underwriting risk (LR) and COVID-19 were included as control variables. To achieve the research goal, the feasible generalized least squares (FGLS) model was applied. The study found a negative effect of the rate of reliance on insurance on the profitability of private insurance companies operating in Syria, while the study did not find a statistically significant effect of the rate of reinsurance on the profitability of the insurance companies under study. The study recommended working to reduce reliance on reinsurance, and adopting a mechanism through which insurance companies can know the risks that must be waived and the risks that they can keep.
Keywords: reinsurance - dependence on reinsurance - profitability - FGLS